Implementasi Metode Percobaan Sederhana Dalam Pembelajaran Sains Di TK It Citra Ummat dan PAUD Arum Melati - Sapil, Nursin; Ismail, Radjiman; Wahid, Santi M. J; Husaen, Rinelsa R. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the implementation of simple trial methods in science learning in IT Kindergarten Citra Ummat and PAUD Arum Melati Tidore Island City. This type of research is descriptive qualitative, which is natural, because the object developed is what it is, not manipulation, and the presence of researchers has no influence on the object. The data sources in this study are teachers and children in Citra Ummat IT Kindergarten and Arum Melati PAUD. The collection techniques are observation, interviews, documentation and triangulation. Research Results The implementation of simple experimental methods in science learning is carried out through several stages, namely: 1) Selection of topics or themes and sub-themes for simple science experiment activities that will be carried out by the way teachers discuss with colleagues or fellow teachers. 2) Objects / Tools and materials or learning media used in introducing science are concrete or real objects. 3) methods used by teachers to introduce science, namely: experimental methods (experiments), demonstrations, questions and answers, telling stories / conversations, field trips and video-based learning. 4) The role of teachers in simple science experiment activities is as facilitator, companion, observer, planner and evaluator. 5) The role of children in the implementation of simple science experiments is that children as observers, inventors and investigators. 6) The results of science experiment activities include cognitive, affective and skill aspects. 7) The process of learning science through simple experiments, namely initial activities in the form of perception, experimental implementation and evaluation activities.